Scientific wisdom in Islam - Khan, Muhammad Razi (Discovery Pub. House, 2011)
Present modest work, namely, Scientific Wisdom in Islam is an endeavout, toward encompassing a vast range of issues, pertaining to Islamic wisdom, between covers.